1993
DOI: 10.1021/bi00097a035
|View full text |Cite
|
Sign up to set email alerts
|

Binding of heparin by type III domains and peptides from the carboxy terminal Hep-2 region of fibronectin

Abstract: The major sites of heparin binding by fibronectin are located in fragments of 30 or 40 kDa that contain type III modules 12 through 14 or 15. Various proteolytic or recombinant subfragments and several synthetic peptides derived from this region have been compared with respect to their binding to fluorescein-labeled heparin in solution. Binding was monitored by the change in fluorescence anisotropy at 25 degrees C and pH 7.4 in 0.02 M Tris buffer, alone (TB) or with 0.15M NaCl (TBS). A 23-kDa fragment containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…The loop connecting strands C-C' would lay on the GFCC'C" face of the AWN model while the N-terminal stretch might not be constraint in a fixed conformation. It is noteworthy that similar to our results concerning AWN 4RRSR8, the RRAR sequence, when present in a synthetic peptide, has been shown to have weak affinity for heparin [28,29]. Furthermore, this same RRAR sequence exists in the carboxylterminal lobe of lactoferrin where it is not functional as a GAG-binding site [30].…”
Section: Discussionsupporting
confidence: 87%
“…The loop connecting strands C-C' would lay on the GFCC'C" face of the AWN model while the N-terminal stretch might not be constraint in a fixed conformation. It is noteworthy that similar to our results concerning AWN 4RRSR8, the RRAR sequence, when present in a synthetic peptide, has been shown to have weak affinity for heparin [28,29]. Furthermore, this same RRAR sequence exists in the carboxylterminal lobe of lactoferrin where it is not functional as a GAG-binding site [30].…”
Section: Discussionsupporting
confidence: 87%
“…This is supported by studies where the use of heparinbinding synthetic peptides led to a reduction of affinity (28,29). As a matter of fact, HepV was shown to fold into the characteristic collagenous structure, the polyproline II helix, by circular dichroism, whereas the peptide tested in the same experimental condition was not (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Interdomain interactions are important determinants of the overall tertiary structure of the protein (20 -22). Fibronectin is able to interact with heparin and heparan sulfate, and there is evidence that this interaction affects the structure of the protein (23)(24)(25)(26)(27)(28). In a previous study, we demonstrated that heparin mediates a conformational change in fibronectin from a compact to a more extended conformation, potentially by interfering with interdomain interactions (29).…”
mentioning
confidence: 85%